Local Delivery of Antitumor Necrosis Factor-α Through Conjugation to Hyaluronic Acid: Dosing Strategies and Early Healing Effects in a Rat Burn Model. Issue 2 (March 2015) - Friedrich, Emily E.; Azofiefa, Andrea; Fisch, Evan; Washburn, Newell R.
Abstract : The objective of this study was to measure dose–response effects of topical delivery of inhibitors of tumor necrosis factor-α (TNF-α) through conjugation to hyaluronic acid in a rat burn model to determine effects on inflammatory responses, burn progression, and early stages of healing. Monoclonal antibodies against TNF-α were conjugated to hyaluronic acid and applied topically in a rat partial-thickness burn model. Metrics of inflammatory responses and tissue necrosis were measured as well as the quantitative analysis of collagen composition and organization. The minimum effective conjugated antibody dose was found to be 100 μ g with three applications 48 hours apart. Nonviable tissue thicknesses decreased with increasing dose and dose frequency. Free antibody retarded macrophage infiltration in the periphery but not at the surface, while the conjugated antibody was able to hinder macrophage infiltration at both the periphery and the surface. Quantification of collagen I and III staining ratios at days 4, 7, and 14 and quantitative image analysis of collagen organization at day 14 demonstrated differences between saline and conjugate treatment. This correlated with increases in re-epithelialization observed in conjugate-treated sites. Reductions in inflammatory markers and secondary tissue necrosis under treatment with the conjugates were understood in terms of differences in antibody transport compared to nonconjugated antibody. Differences in collagen composition and organization at Day 14 suggested that the reductions in inflammatory responses altered early healing responses. These results indicate anti-TNF-α conjugated to hyaluronic acid can be an effective treatment for reducing secondary necrosis and improving healing outcomes in burns.